Society, family, and individual characteristics as double-edged swords in the social reintegration of Iranian female survivors from unintentional severe burns: a qualitative study of enablers and barriers - Masumeh Hemmati Maslakpak; Fardin Ajoudani; Mojgan Lotfi; Vahid Alinejad (BMC, 2021)
Abstract Background Reintegrating to society is a significant challenge during burn survivors' rehabilitation. Aim This study aims to describe what Iranian female survivors from unintentional severe burns experience as enablers and barriers of social reintegration (SR). Methods Fourteen adult female burn survivors whose burns were unintentional participated in this qualitative study. Data were gathered through semi-structured face-to-face or telephone interviews and analyzed using inductive content analysis. Results Thirteen subcategories and six categories were emerged. Categories and subcategories of enablers content area were as follows: positive impact of society on SR (normal treatment of society, instrumental support), positive impact of family on SR (magnifying personal abilities assets, empathy and emotional support), and positive impact of personal characteristics on SR (coping with others stares, right to have a normal social life). Categories and subcategories of Barriers content area were as follows: negative impact of society on SR (being questioned in public, incorrect judgment about intent of burns, burns as a contagious disease), negative impact of family on SR (embarrassment of appearing in public with the survivor, family mistrust), and negative impact of intra-personal factors on SR (exaggeration of the post-burn changes, being over-sensitive to the others looks). From the deep interpretation of the data two overarching themes were emerged: "acceptance of the new normal by the society and the individual" and "being encompassed by misconceptions and mistreatments". Conclusions Society, family and the individual characteristics have a dual role to play in the success of social reintegration in Iranian female unintentional burn survivors.